Human-Related Constraints in Protected Area Management Manifestations and causatives - V ANITHA, P K MURALEEDHARAN, A S BINILKUMAR (Economic and Political Weekly March 11, 2006, 2006)
The establishment of protected areas to conserve and reduce human interactions has resulted in a series of repercussions, which generate new kinds of management issues. Conservation efforts create conflicts among local communities and between the local communities and the enforcing authorities, for they see these efforts as Government-imposed restrictions on their socio-economic system. In this context, this study made an attempt to assess the human-related constraints in management in the Peechi-Vazhani Wildlife Sanctuary, Kerala. It reveals that the constraints relate mainly to an insufficient attention paid to involving local communities and others who care about the protected area in planning, management and decision-making for the area, the social and economic dependencies of the local communities that conflict with the objectives of the PA.